2011
DOI: 10.1089/pho.2011.3016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Laser Therapy in the Treatment of Burning Mouth Syndrome: A Case Series

Abstract: LLLT may be an alternative treatment for the relief of oral burning in patients with BMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 21 publications
2
43
0
2
Order By: Relevance
“…Burning mouth syndrome is a chronic pain condition that adversely affects many aspects of patients' lives (Grushka et al , ; Lopez‐Jornet et al , ; Ni Riordain et al , ). To date, there is no established treatment regimen for BMS; anesthesia and nerve block (Formaker et al , ; Gremeau‐Richard et al , ), laser acupuncture (Romeo et al , ; dos Santos Lde et al , ; Vukoja et al , ; Brailo et al , ), alpha‐lipoid acid (Femiano et al , ; Steele et al , ; Cervigon Gonzalez et al , ; Lopez‐Jornet et al , ), capsaicin (Lauritano et al , ; Petruzzi et al , ; Silvestre et al , ), antidepressants (Kato et al , ; Mignogna et al , ), and benzodiazepines are the most commonly used therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Burning mouth syndrome is a chronic pain condition that adversely affects many aspects of patients' lives (Grushka et al , ; Lopez‐Jornet et al , ; Ni Riordain et al , ). To date, there is no established treatment regimen for BMS; anesthesia and nerve block (Formaker et al , ; Gremeau‐Richard et al , ), laser acupuncture (Romeo et al , ; dos Santos Lde et al , ; Vukoja et al , ; Brailo et al , ), alpha‐lipoid acid (Femiano et al , ; Steele et al , ; Cervigon Gonzalez et al , ; Lopez‐Jornet et al , ), capsaicin (Lauritano et al , ; Petruzzi et al , ; Silvestre et al , ), antidepressants (Kato et al , ; Mignogna et al , ), and benzodiazepines are the most commonly used therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Low power laser radiation therapy has proven to be useful in the reduction of BMS symptoms [71][72][73][74]. On the contrary, Vukoja et al [74] were not able to confirm those results and therefore suggest that the therapeutic benefit of the laser BMS patients was caused by placebo effect.…”
Section: Treatmentmentioning
confidence: 98%
“…On the contrary, Vukoja et al [74] were not able to confirm those results and therefore suggest that the therapeutic benefit of the laser BMS patients was caused by placebo effect. Santos et al [72] had 10 BMS patients undergo to a low power laser session (lowlevel laser therapy -LLLT) once a week over a 10-week span, utilizing the InGaAIP laser diode in continuous mode. A 660 nm wavelength, 40 nW, 20 J/cm 2 of dosimetry and a 0.8 J per point in 10 seconds was used.…”
Section: Treatmentmentioning
confidence: 99%
“…With the use of laser phototherapy on the treatment of BMS, symptoms of burning are reported to decrease, providing pain relief and control of the inflammatory process . Recent studies have shown that the therapeutic effects can be reported by the patient immediately after the irradiation . Also, laser acupuncture (660 nm) has also been reported showing that the technique might be useful in patients with BMS .…”
Section: Introductionmentioning
confidence: 99%